Nursery Rearing of Milkfish, Chanos chanos in Net Cages as a Viable Livelihood Activity by the Self-Help Group of Navsari district, Gujarat - Patil, Pankaj Amrut; Hussain, Tanveer; Khara, Sagar; Bera, Aritra; Kailasam, M; Mahalakshmi, P. (Fishery Technology, 2026)
Polyculture of shrimp (Penaeus vannamei) with milkfish (Chanos chanos) fingerlings is increasingly recognized as a sustainable and profitable method, particularly in coastal regions of Gujarat, India. In shrimp-milkfish polyculture, milkfish fingerlings are cultured with shrimp to maintain pond water quality. However, due to the non-availability of desired stockable-size fingerlings and high transportation costs, shrimp farmers depend on procuring small-sized milkfish seed from southern states of India. Considering the anticipated demand for stockable-size milkfish fingerlings for shrimp polyculture, and to promote milkfish nursery rearing as a livelihood activity, a study was conducted to evaluate production performance, economic and livelihood feasibility of milkfish fry ( 2.3 ± 0.1 cm g) reared at different stocking densities (250, 300, 350, 400, 450, 500 fry/m3) in net cages (2 × 1 × 1 m) installed in ponds (2,500 m³) for a period of 90 days, with participation of Self-Help Group (SHG) in Matwad village, Gujarat. The fish were fed with nursery feed (35.12% crude protein) twice daily (9:00 and 17:00 h) until apparent satiation, and the net cages were cleaned weekly by SHG members. The results indicated that a stocking density of 350 fry/m3 yielded optimal growth (SGR 4.23 %/day; final weight 14.9 g) and survival (88.4%), making it the most economically viable option for commercial nursery operations (net profit ₹6,823 per net cage per cycle; BCR 1.59) compared to other tested densities. The SHG generated a revenue of ₹1.66 lakh in one cycle through the sale of fingerlings (₹13–18 per seed) to shrimp farmers. Overall, the model demonstrates that the milkfish fry nursery rearing (10000 nos) in net cages installed in small ponds (2,500 m³) can generate a net profit of ₹86,901 with minimal labour requirement (2-3 h/day), making it a profitable livelihood activity for SHGs, particularly fisherwomen. This participatory “Technology Transfer Mode” by ICAR-CIBA offers a sustainable employment model for coastal SHGs, enhances shrimp farming sustainability through bioremediation, and helps bridge the demand-supply gap for milkfish fingerlings on the west coast of India.